INVESTMENT ATTRACTIVENESS INDEX FORMULA - N.T.Bozorova (Ethiopian International Journal of Multidisciplinary Research, 2026)
The rapid transformation of Uzbekistan’s economy and the expansion of regional industrial zones have increased the importance of evaluating the investment attractiveness of territorial industrial infrastructure. This article develops a comprehensive scientific model for assessing the investment attractiveness of Regional Industrial Zones (RIZs) and Special Economic Zones (SEZs) in Uzbekistan. The proposed framework integrates infrastructural, financial, administrative, legal, innovative, and environmental indicators into a unified evaluation system based on weighted coefficients and normalization methods. The study also examines the current dynamics of Uzbekistan’s industrial zones using official statistical data and international investment indicators. The article demonstrates that the effectiveness of industrial zones depends not only on fiscal incentives but also on transport connectivity, administrative efficiency, technological modernization, and environmental sustainability. The proposed model can be applied by policymakers, regional authorities, and investors for strategic planning, investment prioritization, and increasing the competitiveness of industrial territories.